Laparoscopic liver resection for huge (≥10 cm) hepatocellular carcinoma: A coarsened exact-matched single-surgeon study. (June 2021) - Kabir, Tousif; Syn, Nicholas L.; Guo, Yuxin; Lim, Kai-Inn; Goh, Brian K.P.
Abstract: Introduction: Laparoscopic liver resection (LLR) is increasingly being utilised worldwide for the management of both benign and malignant liver tumours. However, there is limited data to date regarding the safety and feasibility of this approach for huge (≥10 cm) hepatocellular carcinomas (HCCs). We present here our early experience performing LLR for huge HCCs. Methods: We conducted a retrospective review of 280 consecutive patients who underwent LLR by a single surgeon from 2012 to August 2020.15 patients had a preoperative radiological diagnosis of huge (≥10 cm) HCC. Coarsened exact-matched (CEM) weighting was used to compare them to 101 patients who underwent LLR for non-huge HCC. Results: After CEM-weighting, both groups were well-balanced for baseline variables. There was no difference in the rates of open conversion. The huge HCC patients had a higher mean Iwate difficulty score than the non-huge HCC patients (9.13 vs 6.53, p = 0.007). As such, the median operating time for the huge HCC group was longer (360 min vs 240min, p = 0.049). However, there were no significant differences in estimated blood loss, proportion of patients requiring blood transfusion, utilization of Pringle maneuver or median Pringle duration. Post-operatively, there were no significant differences in median LOS, overall and major morbidity rates, and 90-day mortality rates between both groups. Median resection margins were also similar for both cohorts. Conclusion: LLR may be performed successfully for selected patients with huge HCC, with encouraging perioperative outcomes and no compromise in oncologic efficacy. Highlights: Comparing between LLR for huge HCC and non-huge HCC performed by a single surgeon. Significant longer operation time for huge HCC. No significant difference between the other key perioperative outcomes.